2019
DOI: 10.12659/aot.917767
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of Ubiquitin-Related Genes were Associated with Allograft Fibrosis of Renal Transplant Fibrosis

Abstract: BackgroundInterstitial fibrosis and tubular atrophy (IF/TA) have been recognized as crucial factors contributing to graft loss resulting from chronic renal allograft injuries. Recent studies have indicated a significant association between the progression of organ fibrosis and single nucleotide polymorphisms (SNPs) found on certain genes. Our research sought to understand these potential associations and detect the potential impact of SNPs on ubiquitin-related genes related to allograft fibrosis in kidney tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Pseudogenization of this circadian rhythm regulator may presumably be associated with increased longevity, as well as emerging neoteny in humans [ 24 ]. Gui et al [ 25 ] studied the impact of SNPs in FBXL21 on the success of a kidney transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudogenization of this circadian rhythm regulator may presumably be associated with increased longevity, as well as emerging neoteny in humans [ 24 ]. Gui et al [ 25 ] studied the impact of SNPs in FBXL21 on the success of a kidney transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have found the association of genetic susceptibility with tissue/organ fibrosis such as pulmonary fibrosis, systemic sclerosis, liver and kidney fibrosis [28][29][30][31]. While exogenous factors such as viral hepatitis and alcohol abuse are the common causative factors of liver fibrosis, genetic predisposition may contribute to the progression of fibrosis, cirrhosis, liver failure or hepatic carcinoma [28].…”
Section: Genetic Susceptibility and Expression In Tissue/organ Fibrosismentioning
confidence: 99%